FACTORS ASSOCIATED WITH QUALITY OF LIFE AMONG CANCER PATIENTS RECEIVING EXCLUSIVE PALLIATIVE CARE AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze factors associated with quality of life among cancer patients receiving exclusive palliative care at Nghe An Oncology Hospital.Subjects and methods: A cross-sectional descriptive study was conducted among 130 cancer patients receiving exclusive palliative care at Nghe An Oncology Hospital from February to August 2025. Quality of life was assessed using the EORTC QLQ-C30 version 3.0. Anxiety and depression were evaluated using the HADS scale. Factors associated with quality of life were analyzed using appropriate statistical tests.Results: The mean global health status score according to the EORTC QLQ-C30 was 39.61 ± 22.92. Among functional domains, cognitive functioning had the highest score (56.41 ± 27.94 points), while role functioning had the lowest score (39.10 ± 31.24 points). The symptoms with the greatest impact on quality of life were fatigue (62.30 ± 28.26 points), pain (58.20 ± 33.02 points), insomnia (57.43 ± 33.72 points), and financial difficulties (71.28 ± 30.43 points). Global health status differed significantly between age groups (p = 0.044). Fatigue and pain scores showed statistically significant differences according to disease stage (p = 0.031 and p = 0.013, respectively). Anxiety and depression were negatively correlated with functional domains and global health status, while positively correlated with symptom severity.Conclusion: Cancer patients receiving exclusive palliative care had poor quality of life, which was substantially affected by physical symptoms, functional impairment, financial difficulties, and psychological problems.